(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The following ammonoid and nautiloid taxa are described for the first time from the Upper Triassic succession (Ekrasar Formation, Shemshak Group) of northern Alborz, Iran: Arcestes sp., Arcestes (Pararcestes?) sp., Thisbites cf. agricolae Mojsisovics, Stikinoceras cf. kerri Mc Learn, Giesbachites sp., Griesbachites cf. pseudomedleyanus Diener, Griesbachites cf. himalayanus Wang & He, and Proclydonautilus? sp. Palaeobiogeographically, the studied ammonoids are Tethyan in character, and stratigraphically attributed to the lower Lower Norian (Guembelites jandianus Zone, possibly also Malayites paulckei Zone). The biostratigraphic data of this study demonstrate the diachronous base of the Shemshak Group: it is older in the northern Alborz (lower Lower Norian), but younger in Central Iran and probably also in the southern Alborz (Middle Norian).